2014
DOI: 10.1089/tmj.2013.0275
|View full text |Cite
|
Sign up to set email alerts
|

International Telemedicine Consultations for Neurodevelopmental Disabilities

Abstract: Weekly telemedicine sessions coupled with triannual training conferences were successfully implemented in a clinical program dedicated to patients with neurodevelopmental disabilities by the Center for Neuroscience at CNMC and the UAE government. International consultations in neurodevelopmental disabilities utilizing telemedicine services offer a reliable and productive method for joint clinical programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 5 publications
0
14
0
3
Order By: Relevance
“…4144 Other centers have used telemedicine to provide peer-to-peer sub-specialty consultations 45,46 for developmental disabilities, in their local communities and internationally. 47 One study has even designed a diagnostic tool using home videos recorded by parents. 48 Specifically, a program in Kansas uses professional teams in the patient’s local community to perform standardized assessments, which are then presented to the family and a university-based medical center team that makes the final diagnostic assessment and provides recommendations via telemedicine.…”
Section: Additional Opportunities In Technology and Public Policymentioning
confidence: 99%
“…4144 Other centers have used telemedicine to provide peer-to-peer sub-specialty consultations 45,46 for developmental disabilities, in their local communities and internationally. 47 One study has even designed a diagnostic tool using home videos recorded by parents. 48 Specifically, a program in Kansas uses professional teams in the patient’s local community to perform standardized assessments, which are then presented to the family and a university-based medical center team that makes the final diagnostic assessment and provides recommendations via telemedicine.…”
Section: Additional Opportunities In Technology and Public Policymentioning
confidence: 99%
“…The study presented by Pearl et al [11] demonstrates the reliability and clinical effectiveness of multidisciplinary care incorporating telemedicine in neurodevelopmental disabilities. The program was funded by the UAE government and was implemented through a two-step process involving site visits for initial assessment of healthcare needs and curriculum development for healthcare workers, followed by weekly videoconferencing sessions.…”
Section: A Children's National Medical Center: Specialized Servicesmentioning
confidence: 98%
“…Pilot studies in medically underserved areas have shown improvement in clinical outcomes and this could be the basis for addressing the regulatory issues that have been a barrier to implementation in the United States [10]. Recent use of telemedicine in neurodevelopmental disorders in the United Arab Emirates in conjunction with a number of site visits provided clinical and multi-disciplinary expertise in complex cases, as well as diagnostic workup, management recommendations, and procedural interventions [11]. This was also an invaluable method of providing educational conferences for providers to develop local expertise to support patient care.…”
Section: A Children's National Medical Center: Specialized Servicesmentioning
confidence: 99%
“…Some children will present with normal skills, and will not require a comprehensive assessment. This may improve efficiency and save costs for the service provider (32 Telepractice also offers the opportunity for local SLPs to access educational and mentoring opportunities (131,(138)(139)(140). Telemedicine studies have reported improved communication between local doctors and paediatric subspecialists (138,139,141), with subsequent improvements in the quality and continuity of care (138,139,(141)(142)(143)(144)(145).…”
Section: Figure 6 Possible Telepractice Screening Pathwaymentioning
confidence: 99%
“…However, there is limited evidence to support telepractice for speech pathology management of complex paediatric patients. A literature search (see Chapter 4) found only seven studies that investigated the effectiveness of telepractice for speech pathology service delivery to CMC (33,139,140,(171)(172)(173). None of these studies investigated language screening or assessment, and only three studies examined the use of telepractice for assessment of speech production.…”
Section: Efficacy and Adoption Of Speech Pathology Telepracticementioning
confidence: 99%